Histochemical and Biochemical Alterations in the Stigma of Hibiscus syriacus (Malvaceae) During Flower Development - ÇETİNBAŞ GENÇ, ASLIHAN; VARDAR, FİLİZ (FIRENZE UNIV PRESS, 2019)
The aim of this study is to determine the histochemical and biochemical changes that occurred during flower development in the stigmas of Hibiscus syriacus. The flower development of H. syriacus was divided into three successive stages; pre-anthesis, anthesis, post-anthesis, and stigma development was examined in parallel with these stages. At pre-anthesis, the stigmatic papillae cells covering the surface of the stigma were ovoid and their dense cytoplasm were rich in insoluble polysaccharide, protein and lipid. At anthesis, papillae cells grew and the pellicle layer becomes clear indicating dry-typed stigma. Meanwhile some sub-papillae cells, which accumulate dense organic matter from the beginning of development, began the process of autolysis and release their cellular content into the intercellular space. Whereas the organic matter content of papillae decreased at post-anthesis, it was still more than pre-anthesis stage. Similarly, peroxidase and non-specific esterase activity were very intensive at anthesis stage and activities were still remarkable at post-anthesis stage. The maximum CAT, SOD activity, H2O2 and MDA content were also determined at anthesis. Our results revealed that stigma of H. syriacus is receptive at anthesis and still conserve its receptivity at post anthesis assisting pollen germination and pollen tube growth.
Keywords: Anthesis; antioxidant enzyme; lipid peroxidation; papillae; stigma; OVARY STARCH RESERVES; OLEA-EUROPAEA L.; SELF-INCOMPATIBILITY; SUPEROXIDE-DISMUTASE; PEROXIDASE-ACTIVITY; HYDROGEN-PEROXIDE; POLLEN; RECEPTIVITY; STORAGE; ACID